OPTIMALISASI PEMANFAATAN ARTIFICIAL INTELLIGENCE (AI) DALAM DIGITAL MARKETING UNTUK MENINGKATKAN KOMPETENSI MAHASISWA MENGHADAPI TRANSFORMASI BISNIS DIGITAL - Mulia Aminurahman; Mukhlis Yunus; Muhammad Zikri Farhan; Nurul Fadila; Syarif Lovedly (AbdiMasya | Hira Institute, 2026)
The rapid advancement of Artificial Intelligence (AI) has significantly transformed digital marketing practices through automation, data analytics, and more effective content creation. However, many university students still lack adequate knowledge and practical skills to effectively utilize AI in digital marketing activities. This community service program aimed to enhance students' digital literacy and competencies in applying AI to digital marketing through an interactive online seminar conducted via Zoom Meeting. The program involved 180 participants from the Digital Business, Entrepreneurship, Economic Education, and Elementary School Teacher Education (PGSD) Study Programs at Universitas Merangin. An educational and participatory approach was employed through presentations delivered by practitioners and academics with expertise in digital marketing and artificial intelligence, followed by interactive discussions and question-and-answer sessions. The program was evaluated using a Google Forms questionnaire. The results showed that 94.1% of participants gained new insights into the application of AI in digital marketing, 91.7% felt better prepared to use AI tools to support digital marketing activities, and 89.4% perceived the online seminar as effective and interactive. These findings indicate that AI-based interactive seminars are effective in enhancing students' digital literacy, technology-based marketing competencies, and readiness to adapt to the ongoing digital transformation of the business environment.